DUKUNGAN IBU DALAM MENSTRUAL HYGIENE PADA REMAJA TUNAGRAHITA - Prima Daniyati Kusuma (Jurnal Keperawatan dan Kesehatan, 2021)
Background: The role of parents is very influential in determining how the health of children in the future. Mothers may take on a larger role than fathers, especially in daughter development, due to gender similarities and past experiences. As with the problem of menstruation, it is certain that the mother has more experience than the father. The first menstruation usually occurs in the age range of 10-16 years or in early adolescence in the middle of puberty before entering the reproductive period. Objective: To determine the description of maternal support for mentally retarded adolescents in dealing with menstruation. Method: This research uses descriptive analytical research method, which is a research method conducted to create an objective picture or description of a situation. The sample in this study were mothers with mentally retarded adolescent children. The sampling technique used is total sampling. Results: Emotional support for menstrual hygiene in mentally retarded children is in the good category of 50% and 50% sufficient. Apprecition support for menstrual hygiene in mentally retarded children is in the sufficient category (57.1%). Instrumental support for menstrual hygiene in mentally retarded children is in the sufficient category (85.7%). Informational support for menstrual hygiene in mentally retarded children is in the sufficient category (71.4%). Conclusion: The aspects contained in the social support of menstrual hygiene from the mother, namely informational support, appreciation support, instrumental support, and emotional support play a significant role in influencing menstrual hygiene behavior. Keywords: maternal support, menstrual hygiene, mental retardation